2009
DOI: 10.1093/geront/gnp041
|View full text |Cite
|
Sign up to set email alerts
|

Individual Decision Making in the Non-Purchase of Long-Term Care Insurance

Abstract: States are seeking to offset escalating Medicaid long-term care expenditures through a variety of policy mechanisms, including stimulating individual purchase of long-term care insurance. Findings suggest that economic incentives such as lowering premiums will be necessary but not sufficient to attract appropriate candidates. Attention to behavioral and psychosocial factors is essential to designing incentives that are responsive to concerns and preferences of potential purchasers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 28 publications
1
20
0
Order By: Relevance
“…Although this was a cross-sectional study, several couples articulated an intention to purchase LTCI or self-insure at a time when their personal financial situations allowed. Similar to research on general couple decision-making (Adams 2004;Cramer 2001), study findings suggested that financial LTC planning may not be as static as previous research has suggested (Curry et al 2009;Cramer and Jensen 2006;MetLife Mature Market Institute 2009). Couples may choose to change their financial LTC intentions as well as behaviors as they get older and the risk of LTC becomes more eminent.…”
Section: Financial Ltc Planning Outcomessupporting
confidence: 75%
See 1 more Smart Citation
“…Although this was a cross-sectional study, several couples articulated an intention to purchase LTCI or self-insure at a time when their personal financial situations allowed. Similar to research on general couple decision-making (Adams 2004;Cramer 2001), study findings suggested that financial LTC planning may not be as static as previous research has suggested (Curry et al 2009;Cramer and Jensen 2006;MetLife Mature Market Institute 2009). Couples may choose to change their financial LTC intentions as well as behaviors as they get older and the risk of LTC becomes more eminent.…”
Section: Financial Ltc Planning Outcomessupporting
confidence: 75%
“…Most of these studies have focused on understanding behaviors in regards to LTCI as one financing alternative (AARP 2009;AHIP 2007;Curry et al 2009;Cramer and Jensen 2006;Mellor 2000;MetLife Mature Market Institute 2009;Schaber and Stum 2007;Swamy 2004). Some studies have explored intentions as well as behaviors and found that the majority of individuals who did not purchase LTCI intended to buy LTCI in the future (AHIP 2007;Swamy 2004).…”
Section: Financial Ltc Planning Behaviorsmentioning
confidence: 99%
“…Asymmetric information results in adverse selection 139, 141, 142, 143. In addition, consumer irrationality in the forms of myopia, underestimation of one's risk of needing LTSS, narrow framing, and bounded rationality further contribute to the low uptake of LTCI 1, 144, 145, 146, 147, 148. In regard to bounded rationality, many Americans are unaware that LTCI exists, that they are eligible for coverage, or that their existing health care insurance plans do not cover LTSS 144, 149.…”
Section: Ltss Financing Ideas From Singaporementioning
confidence: 99%
“…We know from prior research that individuals' decisions regarding planning and paying for LTC are based not only on financial incentives, but also on behavioral factors, as well as family structures (Curry et al, 2009). We also know that there is much more to LTC planning than purchasing LTC insurance or financial planning alone.…”
Section: Discussionmentioning
confidence: 99%
“…It is clear from prior research that both behavioral and psychosocial factors play a large role in these decisions as well (Curry, Robison, Shugrue, Keenan, & Kapp, 2009). We look to existing models to guide our understanding.…”
Section: Introductionmentioning
confidence: 99%